SARS-CoV-2 convalescence and hybrid immunity elicits mucosal immune responsesResearch in context - Olha Puhach; Mathilde Bellon; Kenneth Adea; Meriem Bekliz; Krisztina Hosszu-Fellous; Pascale Sattonnet; Nicolas Hulo; Laurent Kaiser; Isabella Eckerle; Benjamin Meyer (EBioMedicine, 2023)
Summary: Background: Mucosal antibodies play a key role in the protection against SARS-CoV-2 infection in the upper respiratory tract, and potentially in limiting virus replication and therefore onward transmission. While systemic immunity to SARS-CoV-2 is well understood, we have a limited understanding about the antibodies present on the nasal mucosal surfaces. Methods: In this study, we evaluated SARS-CoV-2 mucosal antibodies following previous infection, vaccination, or a combination of both. Paired nasal fluid and serum samples were collected from 143 individuals, which include convalescent, vaccinated, or breakthrough infections. Findings: We detected a high correlation between IgG responses in serum and nasal fluids, which were higher in both compartments in vaccinated compared to convalescent participants. Contrary, nasal and systemic SARS-CoV-2 IgA responses were weakly correlated, indicating a compartmentalization between the local and systemic IgA responses. SARS-CoV-2 secretory component IgA (s-IgA) antibodies, present exclusively on mucosal surfaces, were detected in the nasal fluid only in a minority of vaccinated subjects and were significantly higher in previously infected individuals. Depletion of IgA antibodies in nasal fluids resulted in a tremendous reduction of neutralization activity against SARS-CoV-2, indicating that IgA is the crucial contributor to neutralization in the nasal mucosa. Neutralization against SARS-CoV-2 was higher in the mucosa of subjects with previous SARS-CoV-2 infections compared to vaccinated participants. Interpretation: In summary, we demonstrate that currently available vaccines elicit strong systemic antibody responses, but SARS-CoV-2 infection generates higher titers of binding and neutralizing mucosal antibodies. Our results support the importance to develop SARS-CoV-2 vaccines that elicit mucosal antibodies. Funding: The work was funded by the COVID-19 National Research Program 78 (grant number 198412) of the Swiss National Science Foundation.